The jamming transition in high dimension: an analytical study of the TAP equations and the effective thermodynamic potential. (9th September 2016) - Altieri, Ada; Franz, Silvio; Parisi, Giorgio
Abstract: We present a parallel derivation of the Thouless–Anderson–Palmer (TAP) equations and of an effective thermodynamic potential for the negative perceptron and soft sphere models in high dimension. Both models are continuous constrained satisfaction problems with a critical jamming transition characterized by the same exponents. Our analysis reveals that a power expansion of the potential up to the second order constitutes a successful framework to approach the jamming points from the SAT phase (the region of the phase diagram where at least one configuration verifies all the constraints), where the ground-state energy is zero. An interesting outcome is that approaching the jamming line the effective thermodynamic potential has a logarithmic contribution, which turns out to be dominant in a proper scaling regime. Our approach is quite general and can be directly applied to other interesting models. Finally we study the spectrum of small harmonic fluctuations in the SAT phase recovering the typical scaling D ( ω ) ∼ ω 2 below the cutoff frequency but a different behavior characterized by a non-trivial exponent above it.